When young female fans were producing celebrities: The influential factors related to online fan engagement, celebrity worship, and program commitment in idol-nurturing reality shows - Gong, An-Di; Huang, Yi-Ting (Frontiers in Communication, 2022)
Idol-nurturing reality shows that aim to produce idol groups by audience-chosen have become a hotbed for nurturing celebrities. The unique concepts and designs of idol-nurturing reality shows have attracted a group of committed female fans. As a result, the idol-nurturing reality show has become an essential genre of reality shows in the Asian market and an essential part of idol culture. This study concerned the unique concepts and designs of idol-nurturing reality shows and the psychology and behavior of the fans throughout the shows. Results of structural equation modeling based on survey data with 3,352 young Chinese respondents revealed a significant relationship between prompts, motives, online fan engagement, celebrity worship, and program commitment. The data from this study show that the prompts ability, personality, and facial attractiveness positively impacted online fan engagement and that viewing motives social interaction, voyeurism, and suspense positively impacted online fan engagement. In addition, this study found that online fan engagement exerted a significant and positive effect on celebrity worship and program commitment; celebrity worship positively impacted program commitment. This study also provides suggestions on enhancing the fan stickiness of shows and idols.